2008
DOI: 10.3170/2008-8-18463
|View full text |Cite
|
Sign up to set email alerts
|

Importance of soils, topography and geographic distance in structuring central Amazonian tree communities

Abstract: Question: What is the relative contribution of geographic distance, soil and topographic variables in determining the community floristic patterns and individual tree species abundances in the nutrient-poor soils of central Amazonia? Location: Central Amazonia near Manaus, Brazil. Methods: Our analysis was based on data for 1105 tree species (> 10 cm dbh) within 40 1-ha plots over a ca. 1000-km 2 area. Slope and 26 soil-surface parameters were measured for each plot. A main soil-fertility gradient (encompassin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 70 publications
8
88
0
3
Order By: Relevance
“…It has recently been shown that maximum height and H-D relationships are lower in South America than in Asia and Africa (Feldpausch et al 2011, Banin et al 2012, and within Amazonia, trees in the south are shorter than those in the northeast (Nogueira et al 2008b, Feldpausch et al 2011. We propose that this is likely to be a result from the tradeoff between vertical height growth and horizontal crown growth to maximize light capture (King 1996, Aiba and Kohyama 1997, Sterck and Bongers 1998, Bohlman et al 2008. This, in turn, suggests that models with only D and q may be more universal than models with D, q, and H. Indeed, many studies across the tropics have found that trees with greater adult stature and more slender stem allometry are also associated with narrower crowns (Poorter et al 2003, Bohlman and O'Brien 2006, King et al 2006, Aiba and Nakashizuka 2009, Iida et al 2012).…”
Section: Evaluating Existing Modelsmentioning
confidence: 83%
“…It has recently been shown that maximum height and H-D relationships are lower in South America than in Asia and Africa (Feldpausch et al 2011, Banin et al 2012, and within Amazonia, trees in the south are shorter than those in the northeast (Nogueira et al 2008b, Feldpausch et al 2011. We propose that this is likely to be a result from the tradeoff between vertical height growth and horizontal crown growth to maximize light capture (King 1996, Aiba and Kohyama 1997, Sterck and Bongers 1998, Bohlman et al 2008. This, in turn, suggests that models with only D and q may be more universal than models with D, q, and H. Indeed, many studies across the tropics have found that trees with greater adult stature and more slender stem allometry are also associated with narrower crowns (Poorter et al 2003, Bohlman and O'Brien 2006, King et al 2006, Aiba and Nakashizuka 2009, Iida et al 2012).…”
Section: Evaluating Existing Modelsmentioning
confidence: 83%
“…Its eff ects may be related to edaphic factors, light and water availability, and topographic characteristics (Jones et al 2011;PenĂŁ-Claros et al 2012;Baldeck et al 2013;Eisenlohr et al 2013;Oliveira-Filho et al 2013;Sanchez et al 2013;Th uiller 2013). Topography and physicochemical soil properties have been recognized as crucial drivers of vegetation mainly at local scales (e.g., O'Brien et al 2000;Bohlman et al 2008;Machado et al 2008;Souza et al 2012;Toledo et al 2012;MĂ©lo et al 2013). Topography, for example, plays a fundamental role in the description of variations in the composition of vegetation, mainly because a variation in topography may cause alterations in the physical and chemical properties of soils (John et al 2007;Baldeck et al 2013;MĂ©lo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, stochastic processes seem to play a minor but significant role, given that the most species rich genera were similar between close-by areas, as predicted by neutral models. Our findings and an accumulating body of evidence show that forest composition does change along environmental gradients (e.g., Bohlman et al, 2008;Coronado et al, 2009;Engelbrecht et al, 2007;Pitman et al, 2008: Tuomisto, 2006, in spite of the occurrence of widely distributed species along Neotropical forests (Bohlman et al, 2008;Condit et al, 2002). This emphasizes the relevance of protecting in areas of high human preference, because they are usually located in particular ecological settings and floristic composition.…”
Section: Resultsmentioning
confidence: 80%